2021
DOI: 10.3390/cancers13164033
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Surgery after Neoadjuvant Immunotherapy

Abstract: In early-stage lung cancer, recurrences are observed even after curative resection. Neoadjuvant immunotherapy might be a promising approach to eliminate micrometastasis and to potentially reduce recurrence rates and improve survival. Early trials have shown encouraging rates of pathologic response to neoadjuvant therapy and have demonstrated that surgery can be safely performed after neoadjuvant immunotherapy with various agents and in combination with chemo-(radio)therapy. However, whether these response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Moreover, this model is the first prediction model to predict recurrence in stage IA LUAD patients only structured by preoperative blood parameters. Patients with early‐stage LUAD experience local recurrence and distant metastasis due to micrometastasis that cannot be detected by current technology 16,17 . Moreover, previous studies have focused more on postoperative blood parameters, which have led to a delay in the discovery of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this model is the first prediction model to predict recurrence in stage IA LUAD patients only structured by preoperative blood parameters. Patients with early‐stage LUAD experience local recurrence and distant metastasis due to micrometastasis that cannot be detected by current technology 16,17 . Moreover, previous studies have focused more on postoperative blood parameters, which have led to a delay in the discovery of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the reduction of lymph node involvement and the size of the tumor can result in the resectability of the tumor and also increase the chances of obtaining an anatomically and oncological valid resection (lobectomy or bilobectomy), which is safer than pneumonectomy in terms of morbidity and mortality. Interestingly, new perspectives are developing in terms of the pathological response, with the inclusion of immunotherapy in neoadjuvant settings, with the hope that a good complete response rate may lead to improved survival [24].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic immuno-chemotherapy without RT might provide a favorable pathologic response. The efficacy and safety of cICRT shall be examined in future clinical trials, such as the ESPADURVA trial [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have shown that surgery following chemotherapy with concurrent definitive-dose of radiotherapy is safely performed [ 12 , 13 ]. Again, the safety of surgery following “definitive” cICRT shall be extensively examined in future clinical trials [ 10 ].…”
Section: Discussionmentioning
confidence: 99%